2004
DOI: 10.1016/j.ydbio.2003.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genes from inner ear developmental-stage cDNA subtraction reveals molecular regionalization of the otic capsule

Abstract: Although the gross embryology of inner ear development has been documented for several different vertebrate species at a descriptive level, our understanding of the molecular mechanisms involved remains rudimentary. Therefore, we have used cDNA subtraction and normalization procedures to define genes upregulated in the 13.5dpc mouse inner ear, a developmental stage where inner ear morphogenesis and tissue remodeling is active and differentiation of future hair cells is being initiated. We recovered 33 differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Thus, CYTL1 appears to have originated early in vertebrate evolution, suggesting a possible functions in cartilage and bone development. Indeed, CYTL1 expression has been found in cartilagi-nous tissues, such as mouse inner ear and human articular cartilage (10,11). In our previous study (8), we showed that mouse Cytl1 expression was chondrocyte-specific, and further demonstrated that Cytl1 expression was very low in mesenchymal cells, dramatically increased during chondrogenesis, and decreased during hypertrophic maturation, both in vivo and in vitro.…”
mentioning
confidence: 73%
“…Thus, CYTL1 appears to have originated early in vertebrate evolution, suggesting a possible functions in cartilage and bone development. Indeed, CYTL1 expression has been found in cartilagi-nous tissues, such as mouse inner ear and human articular cartilage (10,11). In our previous study (8), we showed that mouse Cytl1 expression was chondrocyte-specific, and further demonstrated that Cytl1 expression was very low in mesenchymal cells, dramatically increased during chondrogenesis, and decreased during hypertrophic maturation, both in vivo and in vitro.…”
mentioning
confidence: 73%
“…Chao et al (12) demonstrated that CYTL1 could significantly prevent inflammatory arthritis. High CYTL1 expression in cartilaginous tissues (13,14) and proteomics analyses on human osteoarthritic patients (15) further supported that CYTL1 was required for the maintenance of cartilage homeostasis. CYTL1 expression was reportedly also significantly positively correlated with perfluoroalkyl and polyfluoroalkyl substances (16).…”
mentioning
confidence: 85%
“…Cytl1 is a functionally unknown cytokine candidate originally cloned from bone marrow and cord blood mononuclear cells that bear the CD34 surface marker (9). Previous studies report Cytl1 mRNA and protein expression in cartilaginous tissues, including mouse inner ear and human articular cartilage, respectively (10,11). Alignment of the predicted primary amino acid sequences of Cytl1 proteins from multiple species (human, mouse, chicken, and puffer) reveals an N-terminal secretory signal peptide and four ␣-helices, a common characteristic of cytokines.…”
mentioning
confidence: 99%